Peel Strength And Other Related Mechanical Properties Of Composite Sandwich Structures - Halim, Zahurin (2002)
An experimental and numerical investigation of the peel strength and other mechanical properties of composite sandwich structures were conducted. The composite sandwich structure consists of carbon fibre and aramid fibre as facings with either a honeycomb or foam core. The peel strength of both types of composite sandwich structure for use at the flap and aileron was studied. The peel tests showed that the composite sandwich structure with a honeycomb core is stronger than the composite sandwich structure with a foam core. The modes of failures or possible path of crack propagation were also studied. The most critical modes of failure were the adhesion failure to the facing and the adhesion failure to the core. A peel model ling was developed using interface elements and the effect of various modes of failures on the strain energy release rate was evaluated by finite element analysis using LUSAS, a commercial finite element code. A numerical scheme called virtual crack closure scheme was used to calculate the strain energy release rate at the peel front in a peel test specimen. To complement the results on the peel strength, investigations on other related mechanical properties were conducted and comparisons were made with previous works in the reference. The important parameters studied were bending, shear and compression as all of them has a static condition. The results show that experimental, numerical and validations with parametric studies agree well . The tensile test was also conducted experimentally to obtain modulus of elasticity that was required in the computational calculations.